Autonomous vehicles and their interaction with section 2(1) of the Consumer Protection Act 1987 - Hawkey, Didier Tuscan (2024)
Autonomous Vehicles (AVs) have developed rapidly due to the efforts of industry stakeholders such as Tesla. However, concerns remain as to how AVs may interact with English law. The strict product liability regime enacted by the Consumer Protection Act 1987 (CPA) has been identified by the Law Commission and UK Government as the civil law regime most capable of accommodating litigation involving harms caused by an AV and enabling those injured to recover damages.